Applying the Smart Retail Target Management System to promote digital transformation at Vietnamese commercial banks - Phan, Minh Xuân; Le, Trương Trọng Duy (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
The rapid development of modern products and services has brought many conveniences to customers and is the foundation for the development of the digital economy and digital society. And in order to realize this, banks have quickly improved their operations and technology to truly become advanced and developed banks in the new era. The study uses secondary data from commercial banks, domestic and foreign studies on digital transformation activities. The article focuses on clarifying that when commercial banks change their operating model from traditional banking to digital banking, it is necessary to apply new technologies, one of those improved technologies is "Application of Management System". Smart retail target management”. The effectiveness of this application shows that commercial banks invest in promoting digital transformation, specifically the application of new technologies that will support traditional banking operations and promote new products to thrive in the future. coming time to contribute to the success of the digital transformation of commercial banks in particular and the economy in general. Besides presenting the benefits of the Smart Retail Target Management System, the article also proposes some solutions to continue promoting digital transformation at Vietnamese commercial banks.